Synthesis and Characterization of Cu(II) and Pb(II) Complexes of trimethoxycarbonyl thiourea ligands - Jacquelyn, Taring (Universiti Malaysia Sarawak, UNIMAS, 2013)
The thiourea derivatives of 2-(3-(3,4,5-trimethoxybenzoyl)thioureido)propanoic acid and 3-(3-(3,4,5-trimethoxybenzoyl)thioureido)propanoic acid and their Cu(II) and Pb(II) complexes have been successfully synthesized. The structures of the ligands were determined using FTIR, UV, 1H NMR and 13C NMR spectroscopy. The FTIR spectra showed significant stretching vibration of the ligands and complexes that supported the structure. The n → π* transition were shown for ligands and π → π* transition were observed for complexes. The structures for complexes were square planar and the ligands were coordinated to the metal through the carboxylate group and amide.